Peningkatan Produktivitas Usaha Kerajinan Keset Penyandang Disabilitas Kabupaten Gunung Kidul di Masa Pandemi Covid-19 - Edy Purnomo; Ishartiwi Ishartiwi; Bayu Rahmat Setiadi; Eka Ary Wibawa; Angga Damayanto (IKIP PGRI Bojonegoro, 2021)
ABSTRACTPusat Pemberdayaan Disabilitas Mitra Sejahtera (PPDMS) is a disability community in Nglipar District, Gunungkidul Regency which has a doormat craft business. A business that is being pioneered and known to the continent of Europe is the craft from rags. The obstacles that become problems for PPDMS are limited capital and raw materials; production process; product quality; limited human resource conditions; amenities; and marketing. To overcome these problems, the Program Pengembangan Produk Unggulan Daerah (PPPUD) has made an increase in the supply of raw materials with a dropping model; provide accessible mat ATBM machine assistance; increase the variants of the model which has better quality; strengthening entrepreneurship through a strategic business plan; business administration and management; rearrangement of workspace and displays; and marketing products offline and online as well as expanding market networks through domestic and foreign marketplaces. The PPPUD implementation method is multiyear for 3 years with main stages. These stages include: infrastructureization (year-1), business development (year-2), and independent & existing (year-3). The achievements that have been made are an increase in high entrepreneurial interest, an increase in production capacity, an increase in marketing reach, and an increase in turnover.Keywords: doormat crafts, people with disabilities, PPDMS, PPPUDABSTRAKPusat Pemberdayaan Disabilitas Mitra Sejahtera (PPDMS) merupakan komunitas disabilitas di Kecamatan Nglipar Kabupaten Gunungkidul yang memiliki usaha kerajinan keset. Usaha yang sedang dirintis dan dikenal hingga benua Eropa adalah kerajinan keset dari kain perca. Kendala yang menjadi permasalahan PPDMS adalah keterbatasan modal dan bahan baku; proses produksi; kualitas produk; kondisi SDM yang terbatas; fasilitas; serta pemasaran. Untuk mengatasi permasalahan tersebut, Program Pengembangan Produk Unggulan Daerah (PPPUD) ini mengadakan peningkatan pada penyediaan bahan baku dengan model dropping; memberikan bantuan mesin ATBM keset yang aksesibel; memperbanyak varian model yang mimiliki kualitas yang lebih baik; penguatan kewirausahaan melalui business plan yang strategis; pengadministrasian dan pengelolaan usaha; penataan ulang ruang kerja dan display; dan memasarkan produk secara offline dan online serta memperluas jaringan pasar melalui marketplace dalam dan luar negeri. Metode pelaksanaan PPPUD adalah multiyear selama 3 tahun dengan tahap-tahap utama. Tahap tersebut meliputi: infrastrukturisasi (tahun ke-1), pengembangan usaha (tahun-2), dan mandiri & eksis (tahun ke-3). Capaian yang telah dilakukan adalah peningkatan minat wirausaha yang tinggi, peningkatan kapasitas produksi, peningkatan jangkauan pemasaran, dan peningkatan omset.Kata Kunci: kerajinan keset, penyandang disabilitas, PPDMS, PPPUD